Leading Maranatha Reformed Church of Christ beyond hundred years through serving and cell groups - Manala, Matsobane J. (HTS teologiese studies, 2024)
This article had as a point of departure, the fact that the most important component of church life and work, was its members, whose edification and enablement were of vital importance. A background was proffered to help the reader acquaint themselves with the church circumstances. An important question in this article was, what would revive and sustain the growth momentum in the 100-year-old plus Maranatha Reformed Church of Christ (MRCC), going forward? I identified the leader’s key performance area as serving God and those who needed his or her gifts, leadership and purpose. This article followed a literary research approach in which various literary sources, especially on the MRCC, servant leadership, practical theology, and cell groups were studied. The aim was to find a solution to the problem of membership decline in this church. Some exploration, interpretation, discernment and discovery was done and achieved, leading to the required solution. A brief definition and discussion of the act of leading through serving and of cell groups were presented. It further, expressed the need to establish and utilise cell groups, as a necessary tool through which the MRCC could attain and sustain needed growth. Having discussed servant leadership, cell groups and their importance, I drew some conclusions.Contribution: This article makes a meaningful contribution to the MRCC, other mainline churches and church growth theoretical studies, by uncovering the resilience and dynamism for church growth residing in servant leadership principles and practices and the utilisation of cell groups.